Predicted quality benefits of achievable performance benchmarks of chronic heart failure care in China: results from a nationwide observational study - Xi Li; Chao Wang; Jingkun Li; Yupeng Wang; Xiaoqiang Bao; Meina Liu; Qiuju Zhang; Chang Yin; Xudong Ma (BMJ Open)
Objectives This study aimed to set a data-driven achievable performance benchmark, explore the process–outcome association and speculate about the net gain in quality improvement with benchmarking.Design Observational study.Setting Patient survey conducted at 466 secondary and tertiary hospitals across 31 provinces, autonomous regions and municipalities in China.Participants 183 334 patients diagnosed with chronic heart failure (CHF) who were treated at 466 Chinese hospitals from January 2011 through May 2017.Primary independent variables Hospital process composite performance (HPCP).Secondary independent variables Patient-level and hospital-level characteristics.Primary outcome measure Patients getting better or recovered after treatment, in-hospital mortality, length of hospital stay (LOS) and medical cost.Methods HPCP was calculated using denominator-based weights. Mixed random-intercept models were used to evaluate the contributions of HPCP on patient outcomes and to speculate quality improvement after adjusting HPCP to benchmark level.Results When all hospitals were to operate at the benchmark level, the proportion of patients getting better or recovered after treatment would increase in most hospitals, particularly those with low baseline rates. However, there was no evidence for lowering in-hospital mortality, significant savings in cost or shortening LOS.Conclusions Increasing the adherence rate of CHF care and closing the gap in HPCP between hospitals have important implications for improving patient condition.